Distal radioulnar joint arthroplasty with implants: a systematic review - Calcagni, Maurizio (EFORT Open Rev, 2016)
A severely painful, dysfunctional, or destroyed distal radio-ulnar joint (DRUJ) can be reconstructed by fusion, interposition of soft tissue, or by arthroplasty using prostheses. The objective of this study was to review the literature on implants and evaluate their effectiveness in terms of pain relief, range of motion and longevity. A search was carried out using protocols and well-defined criteria in PubMed, the Cochrane Library and by screening reference lists. The review was conducted according to PRISMA guidelines. Of the 27 publications reporting on nine different implants, we excluded reports with less than five cases and silastic replacements of the ulna head. Eighteen publications describing a total of five implants were selected for analysis. Nine of the publications were useful for the evaluation of implant longevity. Despite methodological shortcomings in many of the source documents, a summary estimate was possible. It seems that DRUJ implants have good potential to improve function through pain reduction; an improvement was observed in 17 series, although it was significant in only seven series. Instability is not uncommon with ulna head-only implants, but they cause fewer clinical problems and re-interventions than might be expected. The risk of deep infection is small with the available implants. Overall implant survival in papers with at least five years’ follow-up is 95%, with a slightly better longevity of 98% for the constrained implants. Periprosthetic osteolysis/radiolucency is frequently reported. Its causes and consequences are not clarified. Cite this article: Calcagni M, Giesen T. Distal radioulnar joint arthroplasty with implants: a systematic review. EFORT Open Rev 2016;1:191-196. DOI: 10.1302/2058-5241.1.160008.